Development of Teaching Supplement “RESe-CIG” to Improve Understanding of Respiratory System Concepts and Attitudes towards the Dangers of Vaping - Salsabila, Fitriana; Lisdiana (Universitas Negeri Semarang, 2024)
Cases of e-cigarette use at the youth level have increased, this proves students' lack of knowledge and caring attitude regarding the dangers of vaping. This research aims to develop a teaching supplement